Intracellular trafficking of Potato leafroll virus movement protein in Transgenic Arabidopsis - Sonnewald, Uwe; et al. (Traffic, 2007)
Intracellular trafficking of viral movement proteins (MPs) in plants has mainly been studied using Tobacco mosaic virus MP30 (TMV MP30) as a model system. Because of the limitations of TMV MP30 expression in Arabidopsis thaliana, these studies have mostly been restricted to tobacco plants. Here we present data on the analysis of transgenic Arabidopsis plants expressing Potato leafroll virus 17-kDa movement protein (MP17) fused to green fluorescent protein. MP17 localizes to secondary branched plasmodesmata (PD) in source but not to simple PD in sink tissues, where MP17 is believed to be degraded by proteolysis. To unravel the intracellular transport path of MP17, we analyzed the relevance of the cytoskeleton and of the secretory pathway on MP17 targeting. To this end, a new incubation system for in vivo analysis of immediate and long-term responses of whole Arabidopsis plants to inhibitor treatments was established. Microscopic and histochemical analysis showed that MP17 is targeted to PD in an actinand endoplasmic reticulum-Golgi-dependent manner. In contrast, degradation of MP17 in sink tissues required intact microtubules and occurred at 26S proteasomes. Interestingly, inhibition of the 26S proteasome led to aggregation of MP17 in aggresome-like structures. Formation of these structures could be inhibited by colchicine, as was shown for aggresomes in mammalian cells.
Keywords: 26S proteasome; aggresome-like structure; movement protein; MP17; plasmodesmata